PERSONALITY TYPE AND TRANSLATION PERFORMANCE OF PERSIAN TRANSLATOR TRAINEES - Shaki, Reza; Khoshsaligheh, Masood (Universitas Pendidikan Indonesia, 2017)
The study investigated the relationship between the personality typology of a sample of Iranian translation students and their translation quality in terms of expressive, appellative, and informative text types. The study also attempted to identify the personality types that can perform better in English to Persian translation of the three text types. For that purpose, the personality type and the translation quality of the participants was assessed using Myers-Briggs Type Indicator (MBTI) personality test and translation quality assessment (TQA), respectively. The analysis of the data revealed that the personality type of the participants seemed relevant to the translation quality of all the text types. The translation quality of the participants with intuitive and thinking types was significantly better than the sensing type counterparts in translating expressive texts. The participants with intuitive and feeling types also performed better than their counterparts with sensing type in translation of the informative text. Moreover, the participants with intuitive, feeling, and thinking personality types performed more successfully than the participants with sensing type in translation of the appellative text. The findings of the study are discussed in light of the existing research literature.Â